Comparative genomics of a novel clade shed light on the evolution of the genus Erysipelothrix and characterise an emerging species - Grazziotin A.L. (2021)
© 2021, The Author(s).Erysipelothrix sp. isolates obtained from a deadly outbreak in farmed turkeys were sequenced and compared to representatives of the genus. Phylogenetic trees—supported by digital DNA:DNA hybridization and Average Nucleotide Identity—revealed a novel monophyletic clade comprising isolates from pigs, turkeys, and fish, including isolates previously described as E. sp. Strain 2. Genes coding for the SpaC protein, typically found in E. sp. Strain 2, were detected in all isolates of the clade. Therefore, we confirm E. sp. Strain 2 represents a unique species that may be isolated from a broad host range, and the name “Erysipelothrix takahashiae” is suggested. Core genome analysis showed that the pathogenic species of this genus, E. rhusiopathiae and the clade E. sp. Strain 2, are enriched in core functionalities related to nutrient uptake and transport, but not necessarily homologous pathways. For instance, whereas the aerobic DctA transporter may uptake C4-dicarboxylates in both species, the anaerobic DcuC transporter is exclusive of the E. sp. Strain 2. Remarkably, the pan-genome analysis uncovered that genes related to transport and metabolism, recombination and repair, translation and transcription in the fish isolate, within the novel clade, have undergone a genomic reduction through pseudogenization. This reflects distinct selective pressures shaping the genome of species and strains within the genus Erysipelothrix while adapting to their respective niches.